CONDITIONS OF COMPACTION AND DEVELOPMENT OF DIAGENETIC MICROSTRUCTURES IN THE DAFLA AND SUBANSIRI SANDSTONES, WESTERNARUNACHAL PRADESH, INDIA - T. K. Goswami; R.K Sarmah (European Scientific Journal, ESJ, 2013)
The Neogene Siwalik sequence of western Arunachal Pradesh comprises northward dipping thrust sheets structurally below the Main Boundary Fault (MBT) and above the Main Frontal Thrust (MFT). The Sub-Himalayan fold and thrust belt comprises four lithotectonic units between MBT and MFT. From oldest to the youngest these units are Kimi, Dafla, Subansiri and Kimin Formations. The Kimi Formation is equivalent to Lower Siwalik; Dafla and Subansiri formations are equivalent to the Middle Siwalik, while the Kimin Formations represent Upper Siwalik respectively. In the Kameng sector, Tipi Thrust is interpreted to be an intraformational thrust within Subansiri Formation; the Dafla Formations are trusted over the Subansiri Formation relatively at a higher structural level.Compaction and subsequent strong horizontal north to south compression led to the development of numerous zones of cataclasis in the Dafla and Subansiri sandstones. Earlier diagenetic fabrics in the sandstones have been modified considerably due to subsequent development of deformational grain scale microstructures under compression. The Pure Compaction Bands were formed in the initial stage under raised porosity and permeability. These are transformed to Shear Enhanced Compaction Bands and subsequently to Compactional Shear Bands when deformation assumes a simple shear mode under low porosity and permeability value. Higher degree of compaction is evident in the Dafla sandstone compared to that of the Subansiri sandstone which inferred on the basis of the type of the grain contacts, grain packing, frequency of pressure solution seams and segregated micaceous bands.